2015
DOI: 10.1371/journal.pone.0098716
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Effectiveness of the 2011–2012 Seasonal Influenza Vaccine in Adult Korean Populations

Abstract: BackgroundThe effectiveness of the 2011–2012 seasonal influenza vaccine was evaluated in adult Korean populations with regard to how well it could prevent laboratory-confirmed influenza and influenza-related complications.Materials and MethodsA retrospective case-control and retrospective cohort study was conducted among patients who visited four selected hospitals from September 2011 to May 2012. The analysis included 1,130 laboratory-confirmed influenza patients. For each influenza case, one control patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Based on these, vaccine effectiveness against H3N2 might be assumed so poor that the increases of ILI incidence rates appeared to be unavoidable during the 2011/12 season. Consistent with this observation, several reports of reduced vaccine effectiveness against the H3N2 virus have been reported from Asia, Europe, and North America [5456] and even from Korea [15]. As demonstrated by the positive correlation between the ILI incidence rates and the number of H3N2 isolates (Fig 1 and S2 Table), the phylogenetic clustering patterns of the HA and NA genes might substantiate its significance with regard to the comprehensive process of vaccine virus selection.…”
Section: Discussionsupporting
confidence: 80%
“…Based on these, vaccine effectiveness against H3N2 might be assumed so poor that the increases of ILI incidence rates appeared to be unavoidable during the 2011/12 season. Consistent with this observation, several reports of reduced vaccine effectiveness against the H3N2 virus have been reported from Asia, Europe, and North America [5456] and even from Korea [15]. As demonstrated by the positive correlation between the ILI incidence rates and the number of H3N2 isolates (Fig 1 and S2 Table), the phylogenetic clustering patterns of the HA and NA genes might substantiate its significance with regard to the comprehensive process of vaccine virus selection.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, the Spanish influenza surveillance system reported low VE in seasons with predominant circulation of influenza A/H3N2 (14). Similarly, in the ROK, circulation of influenza A/H3N2 was dominant in the past 3 years, with reportedly low influenza VE (15,16). Of note, this study showed that influenza vaccination would be beneficial for elderly individuals and those with comorbidities despite statistically insignificant influenza VE.…”
Section: Discussionmentioning
confidence: 56%
“…Due to the limited number of TND studies reporting very severe outcomes, 45,52,88 we could not compute pooled IVE against ICU admission associated with laboratory confirmed influenza. Castilla et al 88 reported a higher IVE against ICU compared to hospitalized influenza and concluded that vaccination lowered the severity of hospitalized cases of influenza.…”
Section: Discussionmentioning
confidence: 99%